Literasi Digital Di Era Pembelajaran Abad 21 - Fitriyani, Fitriyani; Teguh Nugroho, Arief (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
The writing of this community service journal is the result of activities carried out to be able to provide socialization of the importance of understanding digital literacy in the face of learning in the 21st century era. This community service activity was carried out at Mekar Mukti State Elementary School 02, North Cikarang. This activity is carried out as an effort to improve students' abilities through reading literacy activities so as to foster interests and talents in learners from an early age as well as the literacy culture embedded in learners can affect the success rate and ability of learners to understand information analytically, critically, and reflectively